107. Magnetic-resonance-imaging texture analysis predicts early progression in rectal cancer patients undergoing neoadjuvant chemo-radiation. (December 2018) - Biondi, M.; Vanzi, E.; De Otto, G.; Belmonte, G.; Nardone, V.; Cirigliano, A.; Grassi, A.; Carbone, S.F.; Tini, P.; Sebaste, L.; Carfagno, T.; Battaglia, G.; et al.
Abstract : Purpose: The purpose of this retrospective study was to This retrospective study aims to evaluate the potential use of MRI TA to predict the outcome and relapse of locally advanced rectal cancer (LARC) in patients undergoing Chemo-radiotherapy (C-RT) before radical surgery (TME). Methods: This study regarded patients affected to glioblastoma and treated with concomitant postoperative radiotherapy with before surgery MRI exams (T1, This study included patients treated with C-RT (45 Gy + 9 Gy 1, 8 Gy/day and capecitabine) at our Radiation Oncology Unit between January 2010 and December 2015. Another inclusion criterion was the execution of pelvic MRI (T2 and DWI) examinations (1.5-T system, Signa Excite HD, GE) made at baseline, 30 ± 15 days after the end of C-RT and at 9–12 weeks after TME. The use of Mandard score permits to evaluate the tumour regression grade (TRG). To calculate TA parameters calculation and to perform the necessary statistical analysis is possible with the programs LifeX and SPSS. The research of the correlation of TA parameters and multiple prognostic factors with early progression of disease (ePD) was the primary focus of this study. The omission of the variables with the lowest Pearson correlation coefficient permitted to avoid the model overfitting. With k-fold and ROC analysis was possible to validate our performance model. Results: This study included 73 patient38 patients included in this study had characteristic reported in the table. The reliability analysis performed with ICC showed that the TA parameters that resulted significantly reproducible (ICC > 0.70) were 48% for the T2, 56% for the DWI and 84% for the ADC. The figure shows Pearson correlation analysis significant results. Logistic regression also showed a significant association of DWI GLCM Correlation (p:0.006) and T stage (p:0.036), with an overall R2 of 0.641, a ROC AUC of 0.938 (95% CI 0.854–1.00) and a successful k-fold validation. 38 patients included in this study had characteristic reported in the table. The reliability analysis performed with ICC showed that the TA parameters that resulted significantly reproducible (ICC > 0.70) were 48% for the T2, 56% for the DWI and 84% for the ADC. The figure shows Pearson correlation analysis significant results. Logistic regression also showed a significant association of DWI GLCM Correlation (p:0.006) and T stage (p:0.036), with an overall R2 of 0.641, a ROC AUC of 0.938 (95% CI 0.854-1.00) and a successful k-fold validation. Conclusion: This study shows that there is a correlation between TA GLCM parameters ex A non-invasive mathematical analysis of MRI imaging such as TA, can be used to predict the outcome of patients with LARC and may help to the selection of patients who need additional treatments over the classical neoadjuvant C-RT.